Strengthening adolescents’ critical health literacy and scientific literacy to tackle mis- and dis-information. A feasibility study in Switzerland - Fiordelli, Maddalena; Diviani, Nicola; Farina, Ramona; Pellicini, Paolo; Ghirimoldi, Alberto; Rubinelli, Sara (Frontiers in Public Health, 2023)
Objectives We aimed to develop and test the feasibility of a critical health literacy (CHL) and science literacy (SL) training course targeting secondary school students in Switzerland. Methods Using a community-based participatory approach, we developed a two-block training program, the first centered on argumentation skills and the second on scientific skills. We combined an ex-cathedra and a flipped-classroom approach, providing students with a deep understanding of CHL and SL concepts and the translational capability of implementing theoretical notions to real case scenarios. The feasibility study was designed as a one-group pretest-posttest quasi-experiment. Beyond socio-demographics, questionnaires included measures of CHL, SL, trust in science, and perceived quality of the course. Results The curriculum was feasible and well-accepted by the target groups, teachers, and students. Students convincingly specified their perceived personal benefits associated with a positive change in CHL and SL scores after the training course. Conclusion Training CHL and SL in secondary school students is feasible and can improve their competencies. Results from present study can inform a large-scale study.